BENTUK PERLIDUNGAN HUKUM DARI LEMBAGA PERLINDUNGAN SAKSI/KORBAN DI INDONESIA DAN INGGRIS - rifka safia; Elda Meisy Rahmi; Sela Nurhayati (Universitas Tangerang Raya, 2022)
Witness/ victim protection is the granting of a set of rights that can be utilized by witnesses/ victims in the criminal justice prosess, which is carried out by the witness and victim protection : respect for dignity, security, justice, non-discrimination, and legal certainty, the compare how the existing witnesses/ victims in England. The issue raised is regarding the form of legal protection from witness/ victim protection institutions in Indonesia and the UK. Based on the results of research: First, the weakness of the law on the protection of witnesses. One of them is about an independent LPSK, LPSK should be included in a sub-system of criminal justice. The weakness of the law on the protection of witnesses and victims directly hampers the performance of LPSK, so that LPSK cannor effectively carry out their duties and authorities to provide protection for witnesses and victims. Meanwhile, the form of witness and victim protection in the United Kingdom is much more effective whwn compared to Indonesia, because in that country the protection of witnesses and or victims is included in one of sub-systems in criminal justice, namely the witness and victim protection instution under the police so that it makes CPS is more effective.